2014
DOI: 10.1182/blood.v124.21.3628.3628
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon (CRBN) Gene Polymorphisms Predict Clinical Response and Progression-Free Survival in Multiple Myeloma Patients Treated with Lenalidomide: A Pharmacogenetic Study of Immense Consortium

Abstract: Background: Cereblon (CRBN), a subunit of cullin 4-based E3 ubiquitine ligase complex, has been characterized as the main immunomodulatory drugs (IMiDs), thalidomide, lenalidomide and pomalidomide, binding protein that is crucial for their antiproliferative and immunomodulatory properties. Several recent reports have suggested that CRBN gene and protein expression or alternative splicing affect sensitivity to IMiDs in multiple myeloma (MM). It can be speculated that CRBN expression level, alternative splicing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There are a few similar studies performed on MM patients. At the 56th American Society of Hematology Conference, Iskierka‐Jazdzewska et al () presented data describing 169 relapsed/refractory multiple myeloma (RRMM) patients treated with lenalidomide‐based regimen. Patients were evaluated for the effect of 14 selected SNPs located in the CRBN gene coding region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few similar studies performed on MM patients. At the 56th American Society of Hematology Conference, Iskierka‐Jazdzewska et al () presented data describing 169 relapsed/refractory multiple myeloma (RRMM) patients treated with lenalidomide‐based regimen. Patients were evaluated for the effect of 14 selected SNPs located in the CRBN gene coding region.…”
Section: Discussionmentioning
confidence: 99%
“…The rs1714327 G>C and rs1705814 T>C polymorphisms were associated with significantly lower probability of response to treatment ≥ partial response (OR = 0·25, P = 0·0033 and OR = 0·21, P = 0·0041). In addition, one of these genotypes (rs1705814 T>C) was also associated with shorter PFS (OR = 2·49, P = 0·0054) (Iskierka‐Jazdzewska et al , ). Butrym et al () did not find an association between the CRBN rs121918368 C>T polymorphism and response to immunomodulating therapy in patients diagnosed with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the polymorphisms (rs1714327G>C and rs1705814T>C) were associated with significantly lower probability of response to treatment ≥ PR (OR = 0.25, 95% CI 0.10-0.63; p = 0.0033 and OR = 0.21, 95% CI 0.07- 0.61; p = 0.0041). In addition, one of these SNPs, namely rs1705814T>C, was also associated with shorter PFS (OR = 2.49; 95% CI 1.31-4.74; p = 0.0054) [ 36 ]. Butrym et al analyzed two selected SNPs found in the non-coding regions of the CRBN gene (rs711613, rs1045433) in the context of response to treatment in patients diagnosed with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish with non-functional cereblon do not produce the fin defects when exposed to thalidomide, suggesting that thalidomide-induced teratogenicity may occur by binding to the cereblon complex [71]. Since this finding, several clinical reports have shown a correlation between cereblon expression and the response to thalidomide, and its analogs lenalidomide and pomalidomide in the adult condition, multiple myeloma [7275].…”
Section: Animal Models To Study Anti-angiogenic Drugs and Their Actionsmentioning
confidence: 99%